A Comprehensive Comparison of Period Extraction Algorithms for Asteroids with Long Term Observation - Yang Liu; Liming Wu; Tianqi Sun; Pengfei Zhang; Xi Fang; Liyun Cheng; Bin Jiang (Universe, 2021)
The light curve period of an asteroid plays an important role in determining the rotation period, the collision evolution and the YORP effect. There are many period extraction algorithms used to find the light curve period of asteroids with long term observation, which are mainly based on the frequency, time and time–frequency domains. This paper presents a comprehensive and unparalleled comparison of the popular algorithms based on the DAMIT (Database of Asteroid Models from Inversion Techniques) data set to show the statistical results. Considering the quoted period, absolute magnitude, diameter, albedo, time span and number of observations, we analyze the accuracy of five popular methods using the light curve data of 2902 asteroids. We find that although the performance of all the algorithms varies little, Phase Dispersion Minimization (PDM) performs better, followed by Lomb-Scargle (LS), while Conditional Entropy (CE) is not better than the others under certain conditions. We also analyze the cases which are more suitable for searching by frequencies or by periods.